PLMD-like nocturnal movements with mirtazapine - Mattoo, Surendra K.; Mahajan, Sudhir; Sarkar, Siddharth; Nebhinani, Naresh (General hospital psychiatry, 2013)
Mirtazapine is a commonly prescribed antidepressant with sedative properties. We report a case of nocturnal involuntary limb movements developing in an opioid-dependent young man after starting mirtazapine. The involuntary repetitive bilateral leg movements during initial phase of sleep began when mirtazapine was initiated. They continued for 4 days till mirtazapine was stopped and did not recur subsequently. The role of mirtazapine should be considered when a patient on this drug complains of leg movement during early phase of sleep.